A modified sub-optimum adaptive bit and power allocation algorithm in wideband OFDM system - Li Zhen; Wang Weihua; Zhou Wenan; Song Junde (CCECE 2003 - Canadian Conference on Electrical and Computer Engineering. Toward a Caring and Humane Technology (Cat. No.03CH37436), 2003)
OFDM and adaptive transmission are two most promising technique for next generation high data rate mobile communication systems. In this paper, we combine the two techniques and propose a simple and computational efficient adaptive bit and power allocation algorithm for broadband OFDM system. In the algorithm, first the bit and corresponding power are allocated to each sub-carrier according to channel condition, water filling theory and QoS requirement of the user, then the residual power is allocated to the sub-carriers which can use them most efficiently. In this way, this algorithm is efficient while calculation is less complex. Simulation results show the advantages of the proposed algorithm over those of equal bit loading algorithm and original SNR based adaptive allocation method.